Garawa and Yanyuwa songbook : Christian hymns and choruses composed in Garawa (Karrwa) and Yanyuwa, and translated from English by Garawa and Yanyuwa Christians. (Kangaroo Ground, Vic. : Wycliffe Bible Translators, 1991)
Hymns in Garawa and Yanyuwa.
Includes index to first line of songs in three languages.
With parallel English.
Also available in 3 cassettes.
Keywords: Hymns, Australian Aboriginal -- Texts; Garawa language -- Texts; Yanyuwa language -- Texts; Garrwa / Garrawa / Garawa language (N155) (NT SE53-08); Education - Language - Indigenous languages; Music - Church music - Hymns, Choruses and Carols; Yanyuwa / Yanuwa language (N153) (NT SE53-04); Yanyuwa -- Yanuwa language (N153) (NT SE53-04)